Sociedade e cultura: a transmutação da palavra no espaço da notícia-publicidade - Weisz, Isabel Cristina (2010)
This Dissertation is set on the researches of Portuguese language History and Description in the intersection with oral and writing discourse. In this intersection the focus were the journalistic discourse addressed to people who have not many resources to reading. It is the objective this work For reach this objective, we taken as corpus the MetroNews tabloid. It has, nowadays, thirty-six years of establishment and circulation of 120.0000 exemplars by day. This tabloid is distribuited gracefully in the São Paulo city subway stations and although it has been pressed by a private interprise, take the place of a subway aboard journal‟. The interest for this corpus is justified by the question about which would be the linguistic resources used to communicate news and publicity to a heterogeneous and diffused public who, hipotetically, don‟t have a natural condition to read newspapers cause accepts to take a tabloid for free. Foreback this question there another which search to identify the publisher way to construct your readers image to, far from, it to be able to create a tabloid on demand be understood by his specific public; the subway traveler. The theoretical-metodology observes the stages the tabloid run to be able to accomplish it objective: make publishing The answer for these complexes questions will offer a view over who speaks what and how for who and for which purpose. In this answer comprises the existence of this Dissertation